2021
DOI: 10.1029/2021jc017269
|View full text |Cite
|
Sign up to set email alerts
|

FRIS Revisited in 2018: On the Circulation and Water Masses at the Filchner and Ronne Ice Shelves in the Southern Weddell Sea

Abstract: The Antarctic continent stores the largest amount of freshwater on Earth. However, the Antarctic ice sheets and glaciers are losing mass, leading to a cumulative sea level rise of 14 mm since 1979 (Rignot et al., 2019). Some ice mass loss could be linked to changes in the atmosphere, such as the warming of the Antarctic Peninsula (Vaughan et al., 2003), which triggered the decay of the Larsen ice shelves (Broeke, 2005;Rott et al., 1996). However, the majority of ice mass was lost from glaciers and ice sheets t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 75 publications
(127 reference statements)
3
34
1
Order By: Relevance
“…This would be consistent with recent models of the FRIS cavity circulation which also show this circulation pathway (Bull et al, 2021;Hausmann et al, 2020). The year's delay between the sea-ice low and the high melt rates may be related to the time it takes to gather dense water in the Ronne Depression (Janout et al, 2021), but the exact processes by which the HSSW is transported beneath the ice shelf and how those respond to anomalies in the HSSW volume on the continental shelf remain unknown.…”
Section: Sitesupporting
confidence: 85%
See 4 more Smart Citations
“…This would be consistent with recent models of the FRIS cavity circulation which also show this circulation pathway (Bull et al, 2021;Hausmann et al, 2020). The year's delay between the sea-ice low and the high melt rates may be related to the time it takes to gather dense water in the Ronne Depression (Janout et al, 2021), but the exact processes by which the HSSW is transported beneath the ice shelf and how those respond to anomalies in the HSSW volume on the continental shelf remain unknown.…”
Section: Sitesupporting
confidence: 85%
“…There, Hattermann et al (2021) observed significant inter-annual variations in sub-ice shelf water properties near the Filchner Ice Front, including intermittent intrusions of Berkner HSSW beneath the ice shelf. These dynamics were again related to changes in the circulation strength beneath FRIS that are set by the HSSW forcing originating over the continental shelf north of the Ronne Ice Front (Hattermann et al, 2021;Janout et al, 2021).…”
Section: 1029/2022jc018879mentioning
confidence: 93%
See 3 more Smart Citations